Modlitwa Jezusowa w teorii i praktyce - Hadryś, Jacek (Poznańskie Studia Teologiczne, 2018)
The article presents the problem of Jesus’ prayer both from the theoretical and practical side. It consists of several parts: an explanation of the concept and validity of this type of prayer, a brief presentation of its history, the transformation of structure, main elements, stages, practice and me- aning for spiritual life. The elaboration of the topic was made through analysis and then the synthe- sis of selected documents of the Church and publications on the Name of Jesus and the prayer with that Name. It was stated, inter alia, that Jesus’ prayer is a Trinitarian confession of faith, expresses the love for Christ, enables the activities of the Holy Spirit; brings inner peace, joy, warmth, li- ghtness. Jesus’ Prayer eases self-control, enlightens, permits a person to penetrate into the depths of God’s mysteries, reveals the meaning of Sacred Scripture, causes the person who is praying to consciously stay in God’s presence and to open himself to the saving presence and saving action of the Resurrected Christ. The awareness of God’s presence is in itself motivating to live for Christ.